2003
DOI: 10.4315/0362-028x-66.8.1448
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Distribution of Chiral Compounds in Orange Juices according to Their Geographical Origins

Abstract: Chiral terpenes in nonprocessed orange juices of different geographical origins were examined by two different approaches: steam distillation–solvent extraction–gas chromatography–mass spectrometry (SDE-GC-MS) and solid-phase microextraction–gas chromatography(SPME-GC). The two sample preparation techniques were compared with regard to their effectiveness in determining the enantiomeric distributions of chiral compounds. Most target compounds exhibited constant enantiomeric ratios in all juices when either of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Finally, the correctness of the determined enantiomeric ratios was checked by two independent sample treatment procedures. Del Castillo et al reported significant differences in the enantiomeric ratios of selected chiral terpenes obtained by SPME and steam distillation in nonprocessed orange juices with regard to geographical origin. For this reason, enantiomeric ratios obtained by SPME and LLE were compared.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the correctness of the determined enantiomeric ratios was checked by two independent sample treatment procedures. Del Castillo et al reported significant differences in the enantiomeric ratios of selected chiral terpenes obtained by SPME and steam distillation in nonprocessed orange juices with regard to geographical origin. For this reason, enantiomeric ratios obtained by SPME and LLE were compared.…”
Section: Methodsmentioning
confidence: 99%
“…the mass spectra of the compounds studied were compared to those in the NIST 2012 Library using MSView software. The order of elution of the enantiomers was obtained from data reported in the literature (14,26) and obtained through analysis of the commercial standards.…”
Section: Itmsmentioning
confidence: 99%
“…The chiral compounds selected for this study were those that are most abundant in lemon fruit (α-pinene, β-pinene and limonene), as well as one of the principal odorant compounds (linalool) (27). As shown in Figure 1, two injections with two cuts each one were done, the first one to separate β-pinene from limonene and the second one compounds (14,30). To avoid this high-temperature-induced racemization, SDE at reduced pressure (V-SDE) was tested.…”
Section: Separation Of Target Compoundsmentioning
confidence: 99%
See 2 more Smart Citations